Analysis of the Dimension of Mutual Cooperation in Fables from the Indonesian Language Textbook for Elementary School - Abelia Nabila; Syaiful Bahri; Tri Sukitman (SAINTIS Publishing, 2025)
In the Independent Curriculum (Kurikulum Merdeka), there are six character dimensions of the Pancasila Student Profile designed to cultivate lifelong learners with character, competence, responsibility, and behavior aligned with the core values of Indonesia’s national ideology. One of these essential dimensions is mutual cooperation (gotong royong). This study aims to describe the representation of mutual cooperation values found in fables contained in the Indonesian language textbooks for elementary school students. This research employs a qualitative descriptive method, using content analysis techniques to examine the fable texts. The results of the analysis reveal that there are eight fable stories within the textbook that reflect aspects of the mutual cooperation dimension. From these stories, nine (9) expressions of mutual cooperation are identified. However, the specific element of